Olhos de descobrir: nosso primeiro aprendizado poético de Manoel de Barros - Silva, Alinny Rodrigues Pereira (2019)
This research investigates how is the approximation of the poetic text by students of the second level of elementary school II (6th, 7th grades) of Zênite school (COPAI), in the Inhumas`municipality, inner of Goiás. The poet called was Manoel de Barros, the choice for the author`s work was due to my predilection for the poet and the way how his themes are related to childhood approach of the interests of the public in general, but also to the children. Thus, in order to explore the potentialities of Manoelina`s poetic through the readings undertaken by young readers is that I divide this research in two parts: The first one constitutes in bibliographical analysis with the elaboration of two chapters dedicated to the study of the theoretical contribution which permeates the theories of Aesthetics of Reception, the formation of literary reader, the especificities of poetry teaching, the Manoel de Barros` poetry. In a second moment I start for the application of Manoel de Barros poetry reading workshop in the school field. I collect and analyze the data of students` horizon expectations, so that I observe how is the reception of the poet`s work by the young reader, their readings through of the strategies to transform their conceptions about poetic text and finally, I analyse if there were ruptures or not and the expansion of expectations of this reader public. These data make part of the third chapter which is of analytical character. In order to develop this research, I resorted for theories`assumption of Hans Robert Jauss, Regina Zilberman, Vera Teixeira Aguiar, Maria da Glória Bordini, Élie Bajard, Friedrick, Ebe Siqueira, Hélder Pinheiro, Alexandre Pillati, Elton Souza, among others. I adopt also like references The Parâmetros Curriculares Nacionais de Língua Portuguesa to elementary school I and II (PCN/ 1997) and (PCN/1998).